Was There Any Greed After All? The Lack of Greedflation Evidence in Greek Economic Data - Krompas, Ioannis (HAPSc Policy Briefs Series, 2023)
As Greece has been experiencing a 9.6% inflation in 2022 and 4.2% in 2023, a policy narrative has risen claiming that corporate profits are to blame for the price hikes. However, Greek economic data indicate that when precisely defined, corporate unit profits are within their usual range. Furthermore, publicly available data indicate that corporate mark-ups (price-to-cost ratios) are relatively stable and primarily driven by the increases in costs of goods sold, with a mild increase being attributed to temporary business support measures in force in 2021. In addition, there is the overlooked demand-side component of inflation, contributing up to 50% in price increases between 2021 and 2022, fueled by the country’s fiscal responses to the crises of COVID-19 and the energy crisis of 2021-2022, both of which were among the largest in the world relative to GDP. On top of that, spending of the funds available under the RRF, with Greece once again spending the most in the E.U. relative to its GDP, further contributes to the inflationary pressures. As a result, it is imperative that any government financial support against increasing prices must be better targeted to not work as an income boost, fueling demand side inflation, and that the RRF plan be quickly implemented to lower prices by increasing the country’s productivity, rather than providing widespread income support in the hope of lowering mark-ups and prices only by enforcing competition regulations, which may bring opposite results than those intended.